Comparative study of internal jugular, supraclavicular, and infraclavicular approaches for ultrasound-guided central venous catheterization - Pyakurel, Kumud; Khanal, Kanak; Pokhrel, Anuja; Poudel, Deepak; Dahal, Sonia (Journal of Nepalese Society of Critical Care Medicine, 2023)
Background and aims: Central venous catheterization is a widely used technique in the management of critically ill patients. Ultrasound-guided central venous catheterization has been shown to reduce complications and improve success rates. The internal jugular vein and subclavian vein are common access sites for central venous cannulation. In this study, we aim to compare these approaches in ultrasound-guided central venous catheterization. Methods: A prospective comparative study was conducted at a teaching hospital between August 2022 and January 2023. The study included adult patients requiring central venous catheterization for various indications. Participants were randomly allocated to one of three groups: internal jugular, supraclavicular, or infraclavicular approach. Puncture time, catheter insertion time, guidewire insertion time, success rates, number of attempts, guidewire misplacement, and complications were recorded. Results: The study comprised 143 patients, and there were no significant differences observed between the groups in terms of demographic characteristics. Mean puncture time and catheter insertion time were significantly shorter in the internal jugular group than in the other two groups. There were no significant differences in guidewire insertion time and success rates between the three groups. There were also no significant differences in complications or guidewire misplacement rates between the groups. Conclusion: In ultrasound-guided central venous catheterization, the internal jugular approach had a shorter puncture time and catheter insertion time than the supraclavicular and infraclavicular approaches, with no significant differences in guidewire insertion time, success rates, complications, or guidewire misplacement rates. Internal jugular approach may be the preferred approach for ultrasound-guided central venous catheterization.